(untitled) (KYAMC Journal, 2017)
The simultaneous occurrence of renal cell carcinoma (RCC) in one kidney & stag horn calculus in another kidney is rare combination. We report a 60-year-old man with concurrent large RCC in one kidney & a complete stag horn stone in the opposite kidney. He was admitted to the hospital because of occasional right loin pain and recently diagnosed hypertension leading to the diagnosis of right renal stone and incidental left renal solid mass in ultrasound scan. Contrast enhanced CT scan revealed 8cm x 6 cm irregular contrast enhanced solid mass(RCC)in the left kidney with extension to perinephric fat and 2.5 cm x 1.5 cm stag horn stone with two small caliceal calculi in the right kidney. Open extended pyelolithtomy(Rt) followed by Laparoscopic left radical nephrectomy were performed. Priority, nature of surgery, and post operative residual renal functional status were among the important considerations in this particular case. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 423-426